An integrated method for quantifying and managing extreme weather risks and liabilities for industrial infrastructure and operations. Issue 3 (31st July 2019) - Kytomaa, Harri K.; Boehm, Paul; Osteraas, John; Haddad, Bob; Hacker, Josh; Gilman, Lindsey; Jampole, Ezra; Murphy, Patrick; Souri, Shukri
Abstract: The physical forces and environmental stressors that occur during extreme weather events place facilities at risk for infrastructure failures, loss of operation and production, and highly impactful chemical releases, all of which directly affect a company's bottom line. Hurricane Harvey (2017) resulted in over 100 such failures and chemical releases. There is a pressing need today for risk predictions that incorporate and account for evolving environmental factors such as continuous sea level rise. Such nonstatic (nonstationary) risk management approaches will allow us to more accurately predict storm surge flooding as a function of time and provide more realistic short‐term and long‐term (on the order of decades) predictions to assist in actionable planning. An integrated three‐part approach to assessing the risk of infrastructure damage and chemical releases and the resulting business and legal consequences are presented in this work. This approach consists of (a) temporally variant and spatially localized probabilistic predictions of flooding and forces related to flooding (FloodScore) with unprecedented resolution; (b) detailed impact predictions on facility infrastructure including structural, mechanical, and electrical elements based on the predictions from step (a); and (c) a quantitative means of scoring the environmental/financial risk and consequences of chemicals released as derived from step (b). This integrated approach, which assesses risk of losses in both the near term and out to 50 years in the future, includes the assessment of ecological and human impact levels and provides actionable information for resiliency and risk mitigation planning.